All Days 2013
DOI: 10.2118/167547-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study of Alcohol Mixtures for Enhanced Oil Recovery

Abstract: Several techniques have been deployed to enhance oil recovery. Some have given good results while there is still the possibility that some materials that have not been tried might also have the capacity to enhance recovery. The underlying motivation for this study therefore is to find out the capacity of local materials to enhance oil recovery. Alcohol (palm wine) and water mixture and alcohol (palm wine) and starch mixture were used in various ratios to find out the ideal ratios that recovers oil most from sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The work of Ojo et al (2013) confirmed earlier report that okra has a high recovery rate when used in flooding experiment. Ikeagwu and Adetila (2015) also reported that oil recovery was higher with starch than Irvingia gabonensis. Gbonhinbor and Onyekonwu (2015) experimented with aqueous beans protein to recovery oil and reported a 44% recovery rate; they also recommended it to be used for recovery of heavy oil.…”
Section: Oil Displacement Using Natural Polymersmentioning
confidence: 92%
See 3 more Smart Citations
“…The work of Ojo et al (2013) confirmed earlier report that okra has a high recovery rate when used in flooding experiment. Ikeagwu and Adetila (2015) also reported that oil recovery was higher with starch than Irvingia gabonensis. Gbonhinbor and Onyekonwu (2015) experimented with aqueous beans protein to recovery oil and reported a 44% recovery rate; they also recommended it to be used for recovery of heavy oil.…”
Section: Oil Displacement Using Natural Polymersmentioning
confidence: 92%
“…Some like most cereal products generate visible dust that pollutes the air, with view of the factors highlighted above, environmental issues associated with manufacture of natural polymers can be grouped into; (a) waste water, (b) solid waste, (c) chemical use, and (d) atmospheric pollution (Niu et al 2006). Ojukwu et al (2013) Irvingia gabonensis 22.7 Similar characteristics to Xanthan that is already in use Ikeagwu and Adetila (2015) 1. Cassava starch NS Cassava starch recorded higher recovery than Irvingia gabonensis 2.…”
Section: Environmental Issues Associated With Manufacture Of Natural mentioning
confidence: 98%
See 2 more Smart Citations
“…Their rigid structure and long polysaccharides chains make them suitable to withstand the harsh reservoir conditions. The natural polymers that have been investigated for EOR application at laboratory scale are mushroom and cabbage [18]; Saccharomyces cerevisiae [19]; okra [20]; cassava starch [21]; Detarium microcarpum [22]; gum Arabic [23]; Irvingia gabonensis [21,24]; Brachystegia eurycoma [24]; exudate gum [25]; aqueous beans [26] and schizophyllan [27].…”
Section: ■ Introductionmentioning
confidence: 99%